Slip-Line Metal Cutting Model with Negative Rake Angle - Ozturk, Sabri; Altan, Erhan (ABCM BRAZILIAN SOC MECHANICAL SCIENCES & ENGINEERING, 2012)
A small dead region is seen in front of the rake face of the tool during cutting with negative rake. The lack of knowledge about the stagnant region in the cutting with negative rake requires researching new models. In this work, cutting mechanism of the metal cutting with negative rake angle tools and the stagnation zone formation were studied. A model was generated from the experimental work by usage of the Dewhurst and Collins' matrix technique for solving the slip-line problem numerically. This model was applied at negative rake angles from 0 degrees to -70 degrees. All slip line angles in the slip line model that consist of three regions were resolved with the help of the experimental data. Variation of the dead metal zone and slip line regions with negative rake angle was determined. Effects of the negative rake angle on the cutting and thrust forces were investigated according to the cutting speed.
Keywords: stagnant region; cutting forces; slip-line; negative rake angle; ABRASIVE TOOL; CONTACT; FORCE; MECHANISM; FRICTION; REMOVAL; FLOW; FACE; Engineering